On the Viability and Potential Value of Stem Cells for Repair and Treatment of Central Neurotrauma: Overview and Speculations - Wu, Samantha; FitzGerald, Kevin T.; Giordano, James (Frontiers in Neurology, 2018)
Central neurotrauma, such as spinal cord injury or traumatic brain injury, can damage critical axonal pathways and neurons and lead to partial to complete loss of neural function that is difficult to address in the mature central nervous system. Improvement and innovation in the development, manufacture, and delivery of stem-cell based therapies, as well as the continued exploration of newer forms of stem cells, have allowed the professional and public spheres to resolve technical and ethical questions that previously hindered stem cell research for central nervous system injury. Recent in vitro and in vivo models have demonstrated the potential that reprogrammed autologous stem cells, in particular, have to restore functionality and induce regeneration – while potentially mitigating technical issues of immunogenicity, rejection, and ethical issues of embryonic derivation. These newer stem-cell based approaches are not, however, without concerns and problems of safety, efficacy, use and distribution. This review is an assessment of the current state of the science, the potential solutions that have been and are currently being explored, and the problems and questions that arise from what appears to be a promising way forward (i.e. autologous stem cell-based therapies) – for the purpose of advancing the research for much-needed therapeutic interventions for central neurotrauma.